Java™ After Hours : 10 Projects You'll Never Do at Work - Holzner, Steven (Sams, 2005)
Take your Java programming skills beyond the ordinary. Java After Hours: 10 Projects You'll Never Do at Work will make Java your playground with ten detailed projects that will have you exploring the various fields that Java offers to build exciting new programs. You'll learn to: Create graphics interactively on Web servers Send images to Web browsers Tinker with Java's Swing package to make it do seemingly impossible things Search websites and send e-mail from Java programs Use multithreading, Ant and more! Increase your Java arsenal by taking control of Java and explore its possibilities with Java After Hours .